Contributory Factors to the Inability of the Poor to Access National Health Protection: A Case Study in Waingapu, Sumba Timur District, Indonesia - Windi, Yohanes Kambaru; Harnani, Baiq Dewi; Asnani (Journal of Community Medicine and Public Health Research, 2024)
Millions of poor Indonesians still need access to Indonesia's National Health Protection (NHP). The study investigated barriers making NHP inaccessible for the poor in Waingapu, Sumba Timur, Indonesia.  We used a qualitative approach to identify the contributing factors to why NHP was inaccessible for some populations. A total of 30 residents of Waingapu who attended healthcare in two hospitals and five Community Health Centers were recruited using convenience technic. Twenty residents participated in the semi-structured interview, while ten engaged in casual conversations. We also interviewed three heads of community groups and three health cadres for comparative information. Questions have been developed to guide the interviews and casual conversation. The interviews were audio-taped and transcribed while intensive note-taking was performed during the informal discussion or the conversation was narrated immediately after the talks ended. The information was inductive, analyzed, and coded to produce common information among the participants. The data analysis revealed the factors that contributed to the failure of the resident to enroll in the NHP, such as lack of information about the registration, poor socialization of the program, the ignorance of village officers, unaffordability, and confusion about the parties responsible for the registration. The study concluded that poor people were still vulnerable to access free coverage and healthcare from the NHP. The stakeholders of the NHP, especially the local management of NHP and local government, need to urgently and effectively educate the commoners about the mechanism, benefits, and contribution to the NHP to ensure equity and equality in accessing quality healthcare.